Variations in the Near‐Infrared Spectral Properties of Ferrous Mineral Mixtures With Different Relative Abundances. Issue 9 (16th September 2021) - Zhang, Xunyu; Cloutis, Edward
Abstract: In near‐infrared spectral studies, the relationship between the 1‐μm absorption (Band I) center and the band area ratio (BAR, the area ratio of 2–1‐μm absorption features) is useful in compositional and mineralogical analyses of ferrous mineral‐bearing mixtures. Zhang and Cloutis (2020), https://doi.org/10.1029/2020ea001153, investigated various lunar ferrous iron‐bearing rocks and minerals and found that pyroxene‐bearing materials rich in ilmenite (Ilm), plagioclase (Pl), or glass are offset from the lunar olivine‐clinopyroxene‐orthopyroxene (Ol‐Cpx‐Opx) mixing line in the plot of the BAR versus the Band I center. To analyze the variation trends of the spectral properties of these mixtures with different components, this study presents a systematic evaluation of laboratory spectra of terrestrial and synthetic ferrous iron‐bearing mineral mixtures based on published databases. In general, the mixing trends of the Pl‐pyroxene mixtures, the glass‐pyroxene mixtures, and the Ilm‐basalt mixtures are consistent with the findings of Zhang and Cloutis (2020), https://doi.org/10.1029/2020ea001153 . Moreover, this study also finds that the BAR of the Pl‐pyroxene mixtures varies nonlinearly with different relative abundances and that the BAR is generally not sensitive to Pl abundances below 60%. For glass‐pyroxene mixtures, the corresponding data points are usually appreciably offset from the Ol‐Cpx‐Opx mixing line at glass abundances above 20%. The BAR of the Ilm‐basalt mixtures increases with increasing Ilm content, mainly due to the weakening of 1‐μm absorption generally being greater than that of 2‐μm absorption. Plain Language Summary: Reflectance spectroscopy is a powerful remote‐sensing technique for determining the composition of the Moon's surface. The relationship between two specific spectral characteristics of minerals commonly found on the Moon is useful for analyzing the mineralogical components of iron‐bearing mineral mixtures. These are due to the presence of iron in various phases, and are an important probe into lunar geology. Zhang and Cloutis (2020), https://doi.org/10.1029/2020ea001153, investigated various lunar iron‐bearing rocks and minerals and found that pyroxene‐bearing lunar materials rich in ilmenite (Ilm), plagioclase (Pl), or glass are offset from the lunar olivine‐clinopyroxene‐orthopyroxene (Ol‐Cpx‐Opx) mixing line in the plot of these two spectral characteristics. This study presents a systematic evaluation of laboratory spectra of terrestrial and synthetic iron‐bearing mineral mixtures based on published databases to explain how these mixtures (glass‐pyroxene, Pl‐pyroxene, and Ilm‐pyroxene mixtures) are offset from the lunar Ol‐Cpx‐Opx mixing line. Moreover, this study finds some relationships between the spectral characteristics and the relative abundance of these mixtures. These results expand the range of rock types that are present on the Moon that can be characterized by reflectance spectroscopy. Key Points: The 1‐μm absorption center and band area ratio (BAR) of various natural and synthetic ferrous mineral‐bearing mixtures were analyzed The BAR of the plagioclase‐pyroxene mixtures varies nonlinearly with different relative abundances With increasing ilmenite (Ilm) content, the BAR of the Ilm‐basalt mixtures gradually increases